Aloysius taught Irish in St.John's, reported by Irish Idependent - Mannion,Maura (1981)
Aloysius teaches Irish in St. John's. He studied Irish with the aid of Father O'Growney's books supplemented by records and tapes. Photos of Aloysius and his pupils.